Effects of Sowing Dates and Seed Rates on Sets Yield and Quality of the Red Onion (Allium cepa) cv. ‘Saggai Improved’ (University of Khartoum Journal of Agricultural Sciences, 2023)
An experiment was conducted at Shambat Research Station,Khartoum North for two growing seasons (2003/4 and 2004/5) toinvestigate the effects of three sowing dates (15 Dec., 15 Jan. and 15 Feb.)and five seed rates (90, 100, 110, 120 and 130 kg ha -1 ) on the yield andquality of the sets of red onion cultivar “Saggai Improved” .The firstseason gave the best vegetative growth, high total number and weight ofsets ha -1 as well as improved set quality. High levels of seed ratesincreased the total number of sets ha -1 in the first season, while they hadno effect on growth attributes and size grades per m-2 . However averageset weight decreased when high levels of seed rates were used. Earlyplanting date (15 Dec.) resulted in better plant growth as reflected inincreased leaf number plant-1 , fresh and dry weight of sets and total freshand dry weight. Significant increases in the total number and weight ofsets ha -1 , improved set quality and set weight due to early planting werealso realized
Keywords: onion sets; Allium cepa; sowing date; seed rate